Philosophy And Concepts Of ‘Light’ In Bamboo Shoot Malay Songket Motifs Into Contemporary Lighting Design - Zakaria, Safial Aqbar (2015)
This research focuses on the in-depth meaning and philosophy of light of the songket motifs together with traditions and historical associations. The Malay songket has a unique regional style, which owes its origin and composition to its varied cultural, philosophical and religious backgrounds to help on a development of a creative process in contemporary lighting design. Through songket this research scrutinised the rituals and customs which encompass the philosophy and meanings of light from the Malay interpretation and understandings in terms of culture, spirituality, physical attributes and emotion. The first objective is to analyse the philosophy and meaning of light to the Malays, through an in-depth study of the symbols and motifs of songket. Secondly, this study has interpreted traditional Malay light application and understanding in contemporary context. From the two objectives mentioned above, the third objectives has been established where concepts of contemporary lighting design can be elaborated based on the findings which related to the theoretical interests derived from the songket motifs and transformations into contemporary lighting design practices. The results of this research are qualitative. The research methodology used in this research involved collecting qualitative data. Kajian ini memberi tumpuan kepada makna dan falsafah yang mendalam tentang cahaya motif songket bersama-sama dengan tradisi dan persatuan sejarah. The songket Melayu mempunyai gaya serantau yang unik, yang berhutang asal dan komposisi untuk latar belakang budaya, falsafah dan agama yang berbeza-beza untuk membantu pada pembangunan proses kreatif dalam reka bentuk lampu kontemporari. Melalui songket kajian ini diteliti ritual dan adat yang merangkumi falsafah dan makna cahaya dari tafsiran Melayu dan pemahaman dari segi budaya, kerohanian, sifat-sifat fizikal dan emosi. Objektif pertama adalah untuk menganalisis falsafah dan makna cahaya kepada orang Melayu, melalui kajian yang mendalam mengenai simbol-simbol dan motif songket. Kedua, kajian ini telah ditafsirkan permohonan cahaya tradisional Melayu dan persefahaman dalam konteks kontemporari. Dari kedua-dua objektif yang dinyatakan di atas, objektif ketiga telah diwujudkan di mana konsep reka bentuk lampu kontemporari boleh dihuraikan berdasarkan penemuan yang berkaitan dengan kepentingan teori berasal dari motif songket dan perubahan dalam amalan reka bentuk lampu kontemporari. Keputusan kajian ini adalah kualitatif. Metodologi kajian yang digunakan dalam kajian ini melibatkan pengumpulan data kualitatif.